OXYGEN PRODUCTION TECHNOLOGIES FOR OXY - Katalambula, H (Tanzania Journal of Engineering and Technology, 2017)
Carbon dioxide, a dominating contributor to global warming is emitted to the atmosphere from power plants during combustion of coal. Oxy-fuel combustion is a new technology leading to a simplified sequestration of CO2. In this technology, fossil fuel is combusted with oxygen (instead of air) in such a way that the flue gas primarily consists of CO2, which can then be sequestered without significant processing. Part of the flue gas is used to dilute the oxygen in order to maintain the temperatures in the combustion process. The main energy penalty in oxy-fuel combustion is the cost of oxygen production. There are three major processes for air separation to produce oxygen, these are: cryogenic distillation, membrane separation and gas adsorption. Cryogenic distillation is well established process for large scale production but high energy consumption is the main disadvantage of this process. Membrane and adsorption processes are common for small and medium scale production. In gas adsorption, there are air separation techniques such as pressure and temperature swing methods. The production of oxygen with 90-95% purity and 5000+tpd production is the main challenge for this technology. At present the technology that can supply oxygen in large quantity is the cryogenic separation of oxygen from air. The papers aims at presenting a comprehensive review of the air separation technologies and identify areas that need attention so that oxy-firing can be achieved. The paper therefore looks at different technologies used for oxygen production, economic concepts as well as integration issues in the existing plants.